Development of recipes and estimation of raw material for production of wheat bread - Osokina, K.; Kostetska, O.; Gerasymchuk, V.; Voziian, L.; Telezhenko, O.; Priss, Оlesia; Прісс, Олеся Петрівна; Присс, Олеся Петровна; Zhukova, Valentyna; Жукова, Валентина Федорівна; Жукова, Валентина Федоровна; Verkholantseva, Valentyna; et al. (My University, 2017)
The study of technological parameters of Midas wheat flour and possibility to use little-spread plants at wheat bread manufacturing was realized. Parameters and regimes for keeping and baking bread of new recipes were elaborated and selected. The elaborated method of bread manufacturing by new recipes relates to the field of agriculture and food industry and may be used at a laboratory baking of bread. There was experimentally grounded and introduced the change of a part of recipe quantity of wheat flour for dried and comminuted plants of Népeta mussinii L., Polymnia osotolysta L., Amaranthus tricolor L., Cosmos sulphureus L., Tanacetum parthenium L., Cyperus esculentus L., Physalis tomentous L. at baking bread. According to determined physical-chemical, organoleptic parameters of bread, a possibility of baking bread using plants was proved. The expedience of introducing vegetable additives of Népeta mussinii L., Polymnia osotolysta L., Amaranthus tricolor L., Tanacetum parthenium into wheat dough in the dose no more than 5 % to the flour mass; up to 10 % – Cosmos sulphureus L and up to 15 % – Cyperus esculentus L., Physalis tomentous L was proved. At these very dosages bread had an evenly colored crust, without breaks and cracks, elastic crumb, thin-walled porosity, expressed bread taste and pleasant smell of additives as opposite to other experimental samples.
Keywords: Physalis tomentous L.; Cyperus esculentus L.; Cosmos sulphureus L.; Polymnia osotolysta L.; Amaranthus tricolor L.; Népeta mussinii L.; Tanacetum parthenium L.; new recipes; bread products